Ab initio calculation and kinetic modeling study of diethyl ether ignition with application toward a skeletal mechanism for CI engine modeling. (1st December 2017) - Hu, Erjiang; Chen, Yulin; Zhang, Zihang; Chen, Jyh-Yuan; Huang, Zuohua
Highlights: Geometries, vibrational frequencies and single-point energies were provided. Rate constants of H-abstraction and decomposition reactions were calculated. A detailed DEE chemical kinetic model was proposed. A skeletal kinetic mechanism was developed under engine conditions. Abstract: Quantum chemistry and rate constants of reactions such as H-abstraction of diethyl ether (DEE) by H, OH, HO2, O and CH3 radicals as well as DEE and DEE radicals decomposition and isomerization were carried out through high-level ab initio and RRKM master equation computations. A comparison was made between some of the calculated rate constants and literature data. A detailed kinetic mechanism for DEE ignition contains 341 species and 1867 reactions was developed mainly based on the theoretical calculation and literature data and it was then further compared with the literature measurements along with three other existing DEE models, the Yasunaga model, the Sakai model and the Tran model. Compared with the other three models, the current model can give reasonable predictions on the validated ignition data over a wider temperature range. Based on the current model, a skeletal mechanism which contains 49 species and 192 reactions was developed by using a Jacobian-aided DRGEP approach, followed with a TSA method. The skeletal mechanism can precisely represent the detailed mechanism under a wide range of compression engine related conditions for DEE ignition. Finally, reaction pathway analysis and sensitivity analysis was conducted using the current model to gain an in-depth comprehension on DEE ignition at different temperatures.